Ae dil hai mushkil [videorecording (DVD)] - Johar, Karan, 1972-; Mehta, Apoorva; Johar, Hiroo Yash (Reliance Big Entertainment, 2016)
Ayan falls in love with his soulmate, Alizeh, but she doesn't reciprocate the feeling. Later, a relationship with another woman named Saba helps him realize Alizeh's value in his life, irrespective of their relationship status.